The risk factors for prolonged hemostatic clip retention after endoscopic submucosal dissection for gastric neoplasm - Kim, Sang Hoon; Lee, Jun Kyu; Lim, Yun Jeong; Kim, Jae Hak (Surgical endoscopy, 2022)
Background Endoscopic hemostatic clipping is a safe and efficient treatment used to manage bleeding or perforation during endoscopic submucosal dissection (ESD) for gastric neoplasm. However, the natural history of applied hemoclips during ESD has not been elucidated. As prolonged clip retention limits the use of magnetic resonance imaging and may impede the ulcer healing process, we investigated the factors associated with prolonged hemoclip retention during gastric ESD. Methods We retrospectively reviewed 199 patients who underwent gastric ESD with hemoclip application from January 2006 to January 2019. The primary outcome was the prolonged hemoclip retention rate 3 months after ESD. We examined the records of subjects followed at 3, 6, and 12 months and then annually after ESD to monitor clip retention. Results The prolonged hemoclip retention rate at 3 months was 27.1% (54/199). The risk of hemoclip retention was significantly lower at the antrum (19.6%, P = 0.03). Hemoclips at the angle tended to remain longer than other locations in the stomach (40.6%, P = 0.081) while there was no difference in the number of applied clips depending upon the location of the lesion. By Kaplan–Meier survival analysis, clips at the antrum detached significantly earlier than those at other locations ( P = 0.011). Conclusions Most of the hemostatic clips attached during ESD were spontaneously removed by 3 months after gastric ESD. However, clips positioned at angle are suspected to have a high probability of prolonged retention. With this in mind, more attention is needed when using hemoclips on angle.